(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In the last two decades, post Industrialization cities have been conceived as product of global aspiration and identity. This paper attempts to understand the transformative model of governance adopted in development of the Dholera Special Investment Region in the domain of private partnership and exclusive planning strategies. It explores the role of speculation and making the city a spectacle in the planning of Dholera Special Investment Region. Working on the intersection of these broad theories of the mode of governance, it analyses the Special Investment Region Act, as a facilitator to the growth corridor project and investigates the role of the State in the conceptualization and execution of mega project. The greenfield project reflects the transnational circular economy and urban policies that have brought a paradigm shift in the planning and development of cities in Neo-Liberal Era. It investigates the implications of SIR Act, 2009 on a greenfield project in reference to the right to the city. It argues that for the case of Special Investment Region, Urbanization is seen as a byproduct of the transformative economic and industrial policies.